Analisis Kritik Iklan “Servis Rutin Planet Ban” dengan Pendekatan Bentuk (form), Isi (content), dan Konteks (context) - Paradeva, Atisha Dhuta (CITRAWIRA : Journal of Advertising and Visual Communication, 2022)
In today's technological developments really can not be dammed its existence. Everything in aspects of life began to apply the technological aspect in its application. Included in the field of information. In this field the majority of information has been taken by online media or often also referred to as social media. Youtube is one of the many media. Engaged in the field of video makes it increasingly shift television in everyday life. This is what makes one company in the service sector named Planet Ban start advertising it in the media. This research analyzes by criticizing the advertisement entitled “Servis Routine made by Planet Ban through the approach of form, content, and context.